The Law for the Improvement of the Education Quality (LOMCE) of 2013: one more reform? - Viñao Frago, Antonio (Historia y Memoria de la Educación, 2016)
The Organic Law for the Improvement of the Education Quality (Ley Orgánica para la Mejora de la Calidad Educativa, LOMCE), currently under development and implementation, was passed on December 9, 2013. In this paper we examine its immediate origins, i.e., the failed education agreement promoted by the Socialist Party’s minister Gabilondo in the years 2009-2010. We then tackle the insertion of the LOMCE in the Popular Party’s social and economic policy as well as in the education policy defended by this party and carried out in the Autonomous Communities it governs. Finally, we analyze the short, middle and long term goals of the new reform. This analysis emphasizes the neoconservative features of the new reform and includes some references to its implementation process.